Strategic questions in food and beverage management - Wood, Roy C. 1959- (London Routledge, Taylor & Francis Group, 2018)
This book provides students with a series of critical reviews of issues in food and beverage management addressing a variety of managerial dilemmas of a more complex nature such as how important is the meal experience and is food an art form? These are accompanied by discussion points, questions, and case studies to aid application, critical thinking and analysis.--Provided by publisher.
The former edition was a collection of chapters by various authors; the present work is of sole authorship.
Includes bibliographical references and index.
Keywords: Food service management; Restaurant management; Food service -- Social aspects